Evaluation of real-world mepolizumab use in severe asthma across Europe: the SHARP experience with privacy-preserving federated analysis. Issue 2 (3rd April 2023) - Kroes, Johannes A.; Alfonso-Cristancho, Rafael; Bansal, Aruna T.; Berret, Emmanuelle; Bieksiene, Kristina; Bourdin, Arnaud; Brussino, Luisa; Canhoto, Diogo; Cardini, Cristina; Celik, Gulfem; Csoma, Zsuzsanna; Dahlén, Barbro; et al.
Background: An objective of the Severe Heterogeneous Asthma Registry, Patient-centered (SHARP) is to produce real-world evidence on a pan-European scale by linking nonstandardised, patient-level registry data. Mepolizumab has shown clinical efficacy in randomised controlled trials and prospective real-world studies and could therefore serve as a proof of principle for this novel approach. The aim of the present study was to harmonise data from 10 national severe asthma registries and characterise patients receiving mepolizumab, assess its effectiveness on annual exacerbations and maintenance oral glucocorticoid (OCS) use, and evaluate treatment patterns. Methods: In this observational cohort study, registry data (5871 patients) were extracted for harmonisation. Where harmonisation was possible, patients who initiated mepolizumab between 1 January 2016 and 31 December 2021 were examined. Changes of a 12-month (range 11–18 months) period in frequent (two or more) exacerbations, maintenance OCS use and dose were analysed in a privacy-preserving manner using meta-analysis of generalised estimating equation parameters. Periods before and during the coronavirus disease 2019 pandemic were analysed separately. Results: In 912 patients who fulfilled selection criteria, mepolizumab significantly reduced frequent exacerbations (OR 0.18, 95% CI 0.13–0.25), maintenance OCS use (OR 0.75, 95% CI 0.61–0.92) and dose (mean −3.93 mg·day −1, 95% CI −5.24–2.62 mg·day −1 ) in the pre-pandemic group, with similar trends in the pandemic group. Marked heterogeneity was observed between registries in patient characteristics and mepolizumab treatment patterns. Conclusions: By harmonising patient-level registry data and applying federated analysis, SHARP demonstrated the real-world effectiveness of mepolizumab on asthma exacerbations and maintenance OCS use in severe asthma patients across Europe, consistent with previous evidence. This paves the way for future pan-European real-world severe asthma studies using patient-level data in a privacy-proof manner. This proof-of-principle study using the SHARP federated analysis platform confirms the real-world effectiveness of mepolizumab in 10 European countries. This paves the way for future studies involving thousands of severe asthma patients across Europe. https://bit.ly/3GPsg3T